Efektivitas Hipnoterapi sebagai Intervensi Nonfarmakologis dalam Menurunkan Nyeri Ibu Nifas Pasca Sectio Caesarea - Ahmad Mumtaz Tauba; Yusfina Modesta Rua; Maria Paula Marla Nahak (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Pain following cesarean section (SC) is a major postoperative issue that can disrupt maternal recovery and breastfeeding. Pharmacological pain control alone is often insufficient, hence complementary approaches like hypnotherapy are essential. Objective: The aim of this activity is to enhance the competence of midwives and empower postpartum mothers in managing pain after sectio caesarea surgery through the application of hypnotherapy as a non-pharmacological intervention based on education and hands-on practice at Mgr. Gabriel Manek, SVD Hospital, Atambua. Method: Conducted from September–October 2025 at RSUD Mgr. Gabriel Manek, SVD., Atambua, this activity used an educational quasi-experimental approach involving 30 postpartum mothers and 10 midwives. Participants received training and practical hypnotherapy sessions. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after intervention. Result: The average pain intensity decreased from 4.9 (moderate) to 2.8 (mild) after therapy. 83% of mothers experienced better relaxation and sleep, and 90% of midwives reported increased confidence in using hypnotherapy. From a psychological perspective, hypnotherapy has a significant impact on the emotional stability and self-confidence of postpartum mothers. Participants reported an increased ability to cope with pain without fear and experienced a greater sense of calmness during the recovery period. Conclusion: Hypnotherapy has been proven effective in reducing postpartum pain levels among mothers after sectio caesarea at Mgr. Gabriel Manek, SVD Hospital, Atambua. This program provides physiological, psychological, and educational benefits for postpartum mothers while enhancing midwives’ competence in implementing non-pharmacological interventions. The implementation of this program is recommended to be integrated into maternity care protocols in regional hospitals and adopted as a sustainable training model for healthcare professionals in border areas.